Duration of conventional cardiopulmonary resuscitation prior to extracorporeal cardiopulmonary resuscitation and survival among adult cardiac arrest patients. (April 2016) - Mosca, Matthew S.; Narotsky, David L.; Mochari-Greenberger, Heidi; Liao, Ming; Mongero, Linda; Beck, James; Bacchetta, Matthew
Purpose: The purpose of this study was to evaluate the association between survival and the duration of conventional cardiopulmonary resuscitation (CCPR) prior to extracorporeal cardiopulmonary resuscitation (ECPR) and possible confounding factors. Methods : This was a retrospective analysis of 31 adults who received ECPR at an academic medical center between 2004 and 2013. Odds of 30-day survival and Kaplan Meier survival curves were compared among patients who received CCPR ⩾45 min (n=8, 26%) vs. <45 min (n=23, 74%). Results : There was a trend for greater survival up to 14 days in patients who received CCPR <45 vs. ⩾45 minutes (57% vs. 50%) with no significant difference at 30 days (OR 1.09, 95% CI 0.22-5.45) and survival did not differ by demographic factors. Conclusion : More than half of all patients who received ECPR survived to 30 days. Longer duration CCPR was associated with reduced survival within 2 weeks, but not at 30 days.